Determination and Optimization of Flour for Producing Crispy Baby Tilapia using Plackett Burman Design and Central Composite Design Method - Syamdidi Syamdidi; Diah Ikasari; Hasta Octavini (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2017)
Research on processing of crispy baby tilapia (Oreochromis niloticus) was conducted to obtain type and proportion of flour on this product with central composite design method. This research used 6 types of flour, namely wheat flour, rice flour, potato flour, tapioca flour, corn flour and baking powder. Baby tilapia used for this research were 30-40 day old, 2-3 cm long. Parameters observed were sensory (appearance, odor, taste, texture, overall acceptance) and crispness for the physical parameter. The results showed that only two out of six variables gave big effect on the tested response i.e potato and rice flour. Those two variables were then optimized with central composite design method to obtain the best product. The optimization process demonstrated that the optimum amount of potato and rice flour were 58-60 g (22.16-22.92%) and 40-60 g (15.28-22.92%), respectively.